(untitled) (Journal of Bio-Science, 2018)
Research on species diversity in different gradients of altitudes, aspect and slope is attempting to understand the interactions of vegetation and the non-living environment. The aim of this study was to examine the impact of altitude, slope and aspect variation on the woody species diversity in the Oak forests of Zagros (northern of Iran). 178 samples were taken by using of transect method with a fixed length of 50 m. Altitude, slope, aspect, woody species and diameter at breast height of all trees was recorded in each transect. Margalef richness index, Shannon and Simpson diversity indices and Shannon evenness index were calculated. The Means of the different diversity indices were compared with Kruskal- Wallis test. Results showed that altitude had significant impact on the diversity, richness and evenness of woody species and the middle elevation class (1400 - 1600 m) allocated maximum values of indices. Also, the highest species richness was observed in the (0 - 20%) and (20 - 40%) slope classes but the slope hadn’t effected on the woody species evenness and diversity. The lowest amount of species richness was observed in the east aspect than other aspects. In general, it can be concluded that the altitude had a large proportion of diversity variation than slope and aspect in the research area. J. bio-sci. 23: 19-27, 2015